Effects of cannabidiol and delta-9-Tetrahydrocannabinol on emotion, cognition, and attention: a double-blind, placebo-controlled, randomized experimental trial in healthy volunteers - Wölfl, Timo; Rohleder, Cathrin; Müller, Juliane K.; Lange, Bettina; Reuter, Anne Rebecca; Schmidt, Anna Maria; Köthe, Dagmar; Hellmich, Martin; Leweke, F. Markus (Frontiers in psychiatry, 2020)
The two main phytocannabinoids of cannabis - delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) - have been extensively studied, and it has been shown that THC can induce transient psychosis. At the same time, CBD appears to have no psychotomimetic potential. On the contrary, emerging evidence for CBD's antipsychotic properties suggests that it may attenuate effects induced by THC. Thus, we investigated and compared the effects of THC and CBD administration on emotion, cognition, and attention as well as the impact of CBD pre-treatment on THC effects in healthy volunteers. We performed a placebo-controlled, double-blind, experimental trial (GEI‑TCP II; ClinicalTrials.gov identifier: NCT02487381) with 60 healthy volunteers randomly allocated to four parallel intervention groups, receiving either placebo, 800 mg CBD, 20 mg THC, or both cannabinoids. Subjects underwent neuropsychological tests assessing working memory (Letter Number Sequencing test), cognitive processing speed (Digit Symbol Coding task), attention (d2 Test of Attention), and emotional state (adjective mood rating scale [EWL]). Administration of CBD alone did not influence the emotional state, cognitive performance, and attention. At the same time, THC affected two of six emotional categories - more precisely, the performance-related activity and extraversion -, reduced the cognitive processing speed and impaired the performance on the d2 Test of Attention. Interestingly, pre-treatment with CBD did not attenuate the effects induced by THC. These findings show that the acute intake of CBD itself has no effect per se in healthy volunteers and that a single dose of CBD prior to THC administration was insufficient to mitigate the detrimental impact of THC in the given setting. This is in support of a complex interaction between CBD and THC whose effects are not counterbalanced by CBD under all circumstances.
Gesehen am 01.12.2020